2016
DOI: 10.1200/jco.2016.68.4639
|View full text |Cite|
|
Sign up to set email alerts
|

Pooled Analysis of CNS Response to Alectinib in Two Studies of Pretreated Patients With ALK-Positive Non–Small-Cell Lung Cancer

Abstract: Purpose Alectinib has shown activity in the CNS in phase I and II studies. To further evaluate this activity, we pooled efficacy and safety data from two single-arm phase II studies (NP28761 and NP28673; ClinicalTrials.gov identifiers: NCT01871805 and NCT01801111, respectively) in patients with ALK-positive non-small-cell lung cancer (NSCLC). Patients and Methods Both studies included patients with ALK-positive NSCLC who had previously received crizotinib; all patients received alectinib 600 mg twice per day. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
116
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 20 publications
5
116
0
Order By: Relevance
“…Alectinib is a very promising agent in this setting, since a preclinical study showed that it is not a substrate of P-glycoprotein (P-gp), a key efflux transporter that may impair drug penetration through the blood-brain barrier [18]. Consistently, a pooled analysis of crizotinib-pretreated patients with CNS metastases showed that alectinib provides a CNS-ORR of 64% in individuals with measurable CNS disease (n = 50) [19]. Importantly, other next-generation ALK-TKIs have shown a remarkable activity against CNS metastases, which is crucial in view of the fact that ALK-positive NSCLCs with CNS metastases usually experience a long survival, with median survival potentially exceeding 4 years [20].…”
mentioning
confidence: 61%
“…Alectinib is a very promising agent in this setting, since a preclinical study showed that it is not a substrate of P-glycoprotein (P-gp), a key efflux transporter that may impair drug penetration through the blood-brain barrier [18]. Consistently, a pooled analysis of crizotinib-pretreated patients with CNS metastases showed that alectinib provides a CNS-ORR of 64% in individuals with measurable CNS disease (n = 50) [19]. Importantly, other next-generation ALK-TKIs have shown a remarkable activity against CNS metastases, which is crucial in view of the fact that ALK-positive NSCLCs with CNS metastases usually experience a long survival, with median survival potentially exceeding 4 years [20].…”
mentioning
confidence: 61%
“…The disease control rate (DCR) was detected in 32 (64%) patients with measurable target brain lesions (PR = 22%) and in 37 (43%) patients without measurable target brain lesions (PR = 27%). In patients who underwent radiation therapy of BM (n = 95) before started alectinib therapy intracranial response rate (ICRR) was 35.8% versus 58.5% in patients (n = 41) who did not receive previously radiation therapy [39].…”
Section: Type Of Palliative Treatment Indicationsmentioning
confidence: 99%
“…High RR and DCR were confirmed also stratifying patients according to previous radiotherapy. At the 2015 World Conference on Lung Cancer, a pooled analysis of CNS data from two phase II multicenter studies on patients previously treated with crizotinib (NP28761, NP28673) showed a complete RR of 22%, an ORR of 39% and a DCR of 85% in patients with CNS disease, irrespective of prior radiotherapy (111). The CNS response was sustained for a duration similar to the systemic response, suggesting that alectinib could provide an effective treatment for patients with ALK-positive NSCLC while actively targeting CNS metastases.…”
Section: Efficacy Of Alk Inhibitors On Brain Metastasesmentioning
confidence: 99%